Numerical Investigation of Impinging Planar Shock Wave Interaction with Axisymmetric Slender Body - M. A. Ali; P. Mondal (Journal of Applied Fluid Mechanics)
Shock Wave Boundary Layer Interactions represent a complex flow feature combining high-speed inertial force - dominated flows with low-speed viscous force dominated regions. In this research, planar oblique shock impingement on finned missile body (slender body) have been studied, involving a complex flow field of shocks and expansion waves. Computational studies are used to perform quantitative and qualitative analysis of multi body configurations and investigate the associated flow physics. There is change in induced forces and moments of finned body with change in location of shock impingement, due to the combined effect of enhanced compression, expansion and flow pitch angle on different regions of the missile. For fixed lateral separation between the bodies, changes in coefficient of forces and moments of missile body are very small for shock impingement locations close to fin leading edge. The fins contribute about 50-60% to coefficient of forces and moments of finned missile body. With change in angle of incidence, there is change in polarity of forces and moments illustrating extreme sensitivity of missile body to location of shock impingement, which is due to the combined effect of enhanced compression and expansion on different regions of the missile.